Catalytic effect of commercial carbon-coated nickel nanoparticles on the hydrogen storage performance of magnesium hydride (2025)
Magnesium is an excellent option for hydrogen storage due to its substantial capacity, estimated at approxi- mately 7.6 wt %. However, the desorption temperature usually exceeds 350 ◦C because of slow kinetics and significant thermodynamic stability. Nickel has been used as a catalyst to enhance the kinetics of MgH2 hydrogen desorption and absorption, as well as to reduce the dehydrogenation temperature. Commercial carbon-coated nickel nanoparticles were employed to catalyze hydrogen desorption and absorption in MgH2. These nano- particles were incorporated into the MgH2 through two methods: before and after the ball milling process. Using carbon-coated nickel nanoparticles decreases the onset temperature of dehydrogenation from 321 ◦C in as-milled MgH2 to below 255 ◦C for both sample types containing carbon-coated nickel nanoparticles. The activation energy falls from 152 kJ/mol in as-milled MgH2 to at least 107 kJ/mol, with a minimum value of 81 kJ/mol. During dehydrogenation at 300 ◦C, the best samples evaluated take 10 min to reach 6.38 wt % and 40 min to achieve 5 wt % at 275 ◦C. Furthermore, MgH2 with commercial carbon-coated nickel nanoparticles absorbs 4.5} wt % of hydrogen in 60 min at 150 ◦C and has a retention capacity in hydrogen desorption of 92 % after 10 cycles. Our results suggest carbon-coated nickel nanoparticles can be added to MgH2 without ball milling tocatalyze hydrogen desorption and absorption. This type of catalysis may be appealing for nanosized magnesium- based materials, where ball milling can agglomerate particles or alter a specific morphology.